Role of RNA polymerase I in maintaining the chromatin state of rRNA genes - Fields, Scott, author; Paule, Marvin R., advisor; Laybourn, Paul, committee member; Luger, Karolin, committee member; Suchman, Erica, committee member; Stargell, Laurie, committee member (Colorado State University. Libraries, 2004)
Eukaryotic cells have between 150 and 25,000 copies of rRNA genes that are expressed by RNA polymerase I (pol I), which is its only role in the cell. Psoralen cross-linking showed there are two populations of rRNA genes: nucleosomal and nucleosome free, and cross-linking of pulse-labeled nuclei demonstrated only the latter are actively transcribed. Following DNA replication, all rDNA is packaged by nucleosomes, but about half subsequently get stripped. Pol I has been implicated in nucleosome stripping in yeast, because rRNA genes become nucleosomal in the absence of active pol I. This contrasts with genes transcribed by pol II, which remain nucleosomal during transcription. We found, Acanthameoba castellanii Pol I initiated at the rRNA promoter displaces nucleosomes from DNA in vitro. A nucleosome slows the elongation rate of pol I by approximately two-fold, but elongation eventually Is completed without the aid of other factors or increased ionic strength. Similarly, in vivo, psoralen cross-linking of Saccharomyces cerevisiae rRNA genes that are anomalously transcribed by pol II in a polymerase switch (PSW) mutant revealed the pol I specific nature of pol I stripping as these genes are not stripped of nucleosomes. The ability of pol I to strip nucleosomes plays a key role in maintaining the correct chromatin structure observed for rRNA genes.
Keywords: biochemistry; molecular biology